Design and Development of a Hybrid E-Portfolio Application for Islamic Boarding School Students - Ummi Fadlilatus Zakiyah; Mukarroma, Sofiatun; Amelia Ikmatus Zahro; Ahmad Hamdani (Yayasan Kita Menulis, 2026)
The development of information and communication technology has encouraged educational institutions, including Islamic boarding schools (pesantren), to adopt digital systems for academic management and documentation. One important requirement in pesantren environments is the management of student portfolios that record academic achievements, religious activities, organizational involvement, and community service. However, limited internet access, digital device usage policies, and uneven technological infrastructure hinder the effective implementation of fully online e-portfolio systems. This study aims to design and develop a Hybrid E-Portfolio Application for pesantren students that can be utilized in both offline and online modes. The system was developed using the System Development Life Cycle (SDLC) with a Prototype model, which includes requirement analysis, initial design, prototype development, and user evaluation. The results indicate that the developed system is capable of supporting structured recording, management, and storage of student portfolios, as well as enabling data synchronization when an internet connection is available. The proposed hybrid e-portfolio application provides an adaptive solution to documentation challenges in pesantren environments and supports sustainable digital transformation in pesantren-based education.